Keragaman Spesies dan Genetik Bakteri Staphylococcus pada Ikan Tuna dengan Analisis Sekuen 16s rRNA (SPECIES DIVERSITY AND GENETIC OF STAPHYLOCOCCUS BACTERIA IN TUNA FISH BY USING 16S rRNA SEQUENCE ANALYSIS) - Dewi, Putu Mei Purnama; Besung, I Nengah Kerta; Mahardika, I Gusti Ngurah Kade (Jurnal Veteriner; Vol 16 No 3 (2015), 2015)
Tuna industry belongs to high economic value fish of marine fisheries commodity. Bacteria found intuna might have impact on consumer health. The purpose of this research was to determine the geneticvariation of Staphylococcus in Kedonganan fish market, Kuta, Badung, Bali by sequence analysis of 16SrRNA. Staphylococcus bacteria was isolated from feces samples of 30 tuna. After identification with Gramstaining, Staphylococcus colonies were transferred to the medium chelex 10% for DNA extraction, 16SrRNA gene amplification by polymerase chain reaction (PCR), and electrophoresis. PCR results weresequenced, and the sequence obtained was edited using MEGA 5 and then BLAST was applied to confirmthe species. Genetic variation was determined by analysis of polymorphic sites with MEGA 5. The identifiedbacteria were Staphylococcus sciuri and Staphylococcus haemolyticus. Genetic distance of two isolates S.sciuri are close. The Other species that were identified were Enterococcus faecalis and Macrococcus caseolyticus.Conclusion on this research is Staphylococcus bacteria and two species S.sciuri have many variation.
Keywords: Tuna Fish, Staphylococcus, 16S rRNA sequences, Kedonganan